2014
DOI: 10.1002/cncr.28471
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of erlotinib combined with cisplatin and radiotherapy in patients with locally advanced cervical cancer

Abstract: BACKGROUND: Cisplatin-based chemoradiation (CRT) is the standard treatment for patients with locally advanced cervical cancer. Epidermal growth factor receptor (EGFR) is frequently overexpressed in cervical cancer, and EGFR inhibition itself has antitumor effects and potentiates CRT. Results of a previous phase 1 trial of the EGFR inhibitor erlotinib combined with cisplatin-based CRT (E 1 CRT) recommended a phase 2 erlotinib dose of 150 mg/day. METHODS: Eligibility criteria included International Federation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 36 publications
1
46
0
1
Order By: Relevance
“…Cervical cancer is the third most common cancer among women and the third leading cause of death26. The standard treatment for cervical cancer is cisplatin-based chemotherapy after surgery, which usually yields positive results in initial treatment27. In many cases, however, chemoresistance is induced by prolonged cisplatin-based treatment, which has significant toxicity28.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the third most common cancer among women and the third leading cause of death26. The standard treatment for cervical cancer is cisplatin-based chemotherapy after surgery, which usually yields positive results in initial treatment27. In many cases, however, chemoresistance is induced by prolonged cisplatin-based treatment, which has significant toxicity28.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports may consistently add information about alternative and additional approaches over this standard. 8,21 Neoadjuvant chemotherapy is effective in cervical cancer patients' treatment. The published trial RR observed with NATC varies from 67% to 69% comparing with less than 30% in the metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the systemic treatment of cervical squamous cell carcinoma (CSCC) has advanced into an era of targeted drugs, such as erlotinib (3) and bevacizumab (4), the antitumor efficacies of current therapies are limited, most likely due to the high degree of cancer clonal heterogeneity, intratumoral genetic heterogeneity and cell signal complexity (5). In this context, there is an urgent necessity for more active treatment and rationally designed targeted therapies (6).…”
Section: Introductionmentioning
confidence: 99%